Local Field Effect in antimony-germanate glasses co-doped with Rare-Earth ions and silver nanoparticles - Zmojda, Jacek Mariusz; Miluski, Piotr; Baranowska, Agata; Jadach, Renata; Kochanowicz, Marcin (Photonics Letters of Poland, 2017)
The article presents the possible mechanisms of interaction between emission of Eu3+ ions and surface plasmon resonance (SPR) from Ag0 nanoparticles. The antimony-germanate glasses were synthetized by standard melt-quenching method. The influence of high-phonon glass forming compounds on excitation and luminescence spectra was analysed. Also, we showed that Sb2O3 is a mild reducing agent of noble metal ions. This mild reduction property enables thermochemical reduction of Ag+ to Ag0 in a single-step during the melting process. The energy transfer mechanisms between Eu3+ ions and Ag0 nanoparticles were also discussed in terms of local field effect of Ag0 nanoparticles. Full Text: PDF References S. Chatterjee, S. K. Saha, and D. Chakravorty, "Glass-Based Nanocomposites" in Glass Nanocomposites, B. Karmakar, K. Rademann and A. L. Stepanov, (Eds.: William Andrew Publishing, Boston, 2016) DirectLink D. Dorosz, et al., "Structural and optical study on antimony-silicate glasses doped with thulium ions", Spectrochim. Acta A 134, 608 (2015). CrossRef J. Zmojda, et al., "Effect of GeO2 content on structural and spectroscopic properties of antimony glasses doped with Sm3+ ions", J Mol. Struct. 1126, 207 (2016) CrossRef J. Zmojda, D. Dorosz, M. Kochanowicz, J. Dorosz, "Spectroscopic properties of Yb3+/Er3+ - doped antimony-phosphate glasses for fiber amplifiers", Phot. Lett. Poland 2, 76 (2010) CrossRef M. Eichelbaum and K. Rademann, "Plasmonic Enhancement or Energy Transfer? On the Luminescence of Gold-, Silver-, and Lanthanide-Doped Silicate Glasses and Its Potential for Light-Emitting Devices", Adv. Funct. Mater. 19, 2045 (2009) CrossRef Binnemans, K. Coord. "Interpretation of europium(III) spectra", Chem. Rev. 295, 1 (2015) CrossRef S. Selvi, K. Marimuthu, N. S. Murthy, G. Muralidharan, "Red light generation through the lead boro?telluro?phosphate glasses activated by Eu3+ ions", J Mol. Struct. 1119, 276 (2016) CrossRef J. Zmojda, et al., "Optical Characterization of Nano- and Microcrystals of EuPO4 Created by One-Step Synthesis of Antimony-Germanate-Silicate Glass Modified by P2O5", Materials 10, 1059 (2017) CrossRef N. Shasmal, B. Karmakar, "Enhancement and tuning of photoluminescence properties in Pr3+/Au co-doped antimony oxide glass nanocomposites by thermal treatment", J Alloy. Compd. 688, 313 (2016) CrossRef